2021
DOI: 10.1021/acs.iecr.1c02604
|View full text |Cite
|
Sign up to set email alerts
|

Simple But Tricky: Investigations of Terephthalic Acid Purity Obtained from Mixed PET Waste

Abstract: In this study, we report, for the first time, the basic depolymerization of mixed waste polyethylene terephthalate (PET) by hydrolysis and subsequent terephthalic acid monomer recovery with high purity using benign reaction conditions. Several conditions were tested for depolymerization such as PET chip size, concentration of aqueous sodium hydroxide (20 or 30%), organic co-solvent (ethylene glycol or ethanol), temperature at which the reaction was run, and duration of the heating. More importantly, several pu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
30
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

1
7

Authors

Journals

citations
Cited by 32 publications
(39 citation statements)
references
References 28 publications
3
30
0
Order By: Relevance
“…Powdered, virgin PET for model reactions was purchased from Goodfellow Corporation (Coraopolis, PA). TPA was obtained from mixed-waste PET, composed of colored, clear, and opaque yellow bottles whose labels and caps were not removed, via basic hydrolysis, and the study is reported in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Powdered, virgin PET for model reactions was purchased from Goodfellow Corporation (Coraopolis, PA). TPA was obtained from mixed-waste PET, composed of colored, clear, and opaque yellow bottles whose labels and caps were not removed, via basic hydrolysis, and the study is reported in detail elsewhere …”
Section: Methodsmentioning
confidence: 99%
“…TPA was obtained from mixed-waste PET, composed of colored, clear, and opaque yellow bottles whose labels and caps were not removed, via basic hydrolysis, and the study is reported in detail elsewhere. 9 2.2. Synthesis.…”
Section: Methodsmentioning
confidence: 99%
“…While this paper has focused on mechanical recycling, depolymerization of PET and chemical recycling continue to be active areas of research. Recently, investigators at the Pacific Northwest National Laboratory depolymerized PET bottles with mixed waste of pigments, labels, adhesives, and polypropylene rings . At relatively mild conditions, and using no catalyst, the chopped PET was converted in both ethylene glycol and ethanol in water to generate 97–98% pure terephthalic acid monomer.…”
Section: Resultsmentioning
confidence: 99%
“…Recently, investigators at the Pacific Northwest National Laboratory depolymerized PET bottles with mixed waste of pigments, labels, adhesives, and polypropylene rings. 82 At relatively mild conditions, and using no catalyst, the chopped PET was converted in both ethylene glycol and ethanol in water to generate 97−98% pure terephthalic acid monomer. Examples of other research have examined chemical recycling as pyrolysis of HDPE 83 and pyrolysis and gasification of polypropylene.…”
Section: ■ Results and Discussionmentioning
confidence: 99%
“…A significant finding in Figure is that the presence of PP or cellulose during PET hydrolysis does not increase the amount of byproducts in the solids containing the TPA. Cosimbescu et al studied the byproducts from hydrolysis (with ethylene glycol or ethanol as co-solvents) of pure PET and mixed waste (PET bottles with caps). Their analyses indicated 97–98% purity (based on proton peak areas from NMR) of the TPA irrespective of the components in the initial mixture.…”
Section: Resultsmentioning
confidence: 99%